Drag reduction in single-phase crude oil flow: A mini-review - Farid Souas; Ahmed Salah Eddine Meddour (Journal of Pipeline Science and Engineering, 2022)
It is well recognized that a major issue for fluid flows in many industrial pipe systems, including the transportation of crude oil, is the high energy consumption in the pipeline system brought on by significant pressure losses in turbulent flows. The reduction of apparent viscosity and drag are two important challenges in order to enhance crude oil flow conditions in long-distance pipelines. Chemical techniques are seen to be the most efficient and practical ways to handle these problems. The pressure drop through a pipeline can be decreased by adding a tiny quantity of drag-reducing agents (DRA) to the flow of crude oil, which is a commonly employed approach. As a result, the energy usage drops for a certain flow rate. In the field of reducing crude oil drag, polymer and surfactant additives have been extensively used for this purpose. Therefore, a literature review of published experimental work relating to drag reduction by DRA in single-phase crude oil flow is discussed in this paper in order to better understand the mechanism of the drag reduction phenomena in crude oil pipelines.